A soil safari: on a quest to restore and manage grassland soils - Tam, Kristen (International Livestock Research Institute, 2024)
Kenyan grasslands are under increasing pressure from extreme weather (drought and/or flooding), invasive species, and poor management such as overgrazing. This can cause degradation of the soils beneath, depleting them of nutrients, carbon and life; damaging their structure (e.g. through compaction), and in severe cases causing topsoil to be lost completely through soil erosion. Soil degradation can have long term effects on grassland productivity and resilience. There has been a lot of research on intensively managed grasslands in Europe and the USA, but less on tropical grasslands in semi-arid areas of east Africa. Research has also tended to focus on aboveground communities (plants) and neglect the important role of healthy soils in supporting healthy grassland ecosystems. We still don’t have a good understanding of how the soils underlying Kenyan grasslands, which are different to soils in temperate regions, might respond to different management or restoration interventions.